2016
DOI: 10.1038/nature17197
|View full text |Cite
|
Sign up to set email alerts
|

A 17-billion-solar-mass black hole in a group galaxy with a diffuse core

Abstract: Quasars are associated with and powered by the accretion of material onto massive black holes; the detection of highly luminous quasars with redshifts greater than z = 6 suggests that black holes of up to ten billion solar masses already existed 13 billion years ago 1 . Two possible present-day 'dormant' descendants of this population of 'active' black holes have been found 2 in the galaxies NGC 3842 and NGC 4889 at the centres of the Leo and Coma galaxy clusters, which together form the central region of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(194 citation statements)
references
References 64 publications
16
177
1
Order By: Relevance
“…By combining the above data with the near-infrared J, H, K-band spectra acquired by the Gemini and Magellan telescopes in Chile on 6 August and 7 October 2014, respectively, this quasar BH mass is estimated to be (1.24 ± 0.19) × 10 10 M ⊙ . This is the first evidence for the theoretically predicted HMBHs in the early Universe (z > ∼ 6), even though there are other evidence for HMBHs at lower z [29, 30,31]. Given selection effects, HMBHs and SMBHs should be actually more abundant than what we have detected so far.…”
Section: Observational Evidence For Hmbhs In the Early Universecontrasting
confidence: 47%
See 2 more Smart Citations
“…By combining the above data with the near-infrared J, H, K-band spectra acquired by the Gemini and Magellan telescopes in Chile on 6 August and 7 October 2014, respectively, this quasar BH mass is estimated to be (1.24 ± 0.19) × 10 10 M ⊙ . This is the first evidence for the theoretically predicted HMBHs in the early Universe (z > ∼ 6), even though there are other evidence for HMBHs at lower z [29, 30,31]. Given selection effects, HMBHs and SMBHs should be actually more abundant than what we have detected so far.…”
Section: Observational Evidence For Hmbhs In the Early Universecontrasting
confidence: 47%
“…We have detected numerous SMBHs and a couple of HMBHs in quasars near and far [26,30,31] − the farthest one with high redshift z = 7.085. The most massive quasar is close to…”
Section: Neutral Hydrogen Environments Of Quasars Near and Farmentioning
confidence: 97%
See 1 more Smart Citation
“…More likely their descendants will not be in privileged sites but in rather isolated galaxies (e.g. Thomas et al 2016) Our work and the finding that black hole growth is linked to tidal field theory offers some explanation as to the origin of the most massive BHs in most compact galaxies. It is interesting that Barber et al (2016) using the EAGLE simulation at z = 0 also found a strong link between compactness of the host and the most (positive) outliers in the MBH − M * relation.…”
Section: Discussionmentioning
confidence: 96%
“…Recent progress detecting high-mass black holes in Brightest Cluster Galaxies (BCGs) and other large early-type galaxies hint that these objects may be positive outliers from M BH − σ ⋆ and M BH − L bul (e.g., McConnell et al 2012;Rusli et al 2013;Thomas et al 2016), but there are still too few measurements to firmly characterize the scaling relations at M BH 10 9 M ⊙ . The uncertainties are equally severe at the opposite end, where spiral galaxies with low-mass black holes (M BH 10 7 M ⊙ ) measured from water megamaser disks exhibit substantial scatter below the global black hole -host galaxy relations (e.g., Greene et al 2010;Läsker et al 2016;Greene et al 2016).…”
Section: Introductionmentioning
confidence: 99%